Logística Aplicada à Roteirização e Distribuição de Produtos em Empresas de construção civil - Santos, Tatiene de Castro Andrade (2011)
The decision to search the routes in a particular construction company comes from the need to verify whether Vehicle Routing brought an effective optimization in the fleet, routes and delivery of cargo operations. Trip costs, distances and time were analyzed using TransCAD software, which gives a rich assemble of instruments for vehicle routing and solutions to several troubles. It was chosen the month of January, for being the greatest delivery demand, some parameters were stablished, such as vehicle type, fleet specifications, average demand by client and so one. This study is based on the analyzis of product distribution from three construction companies wich have two distribution centers for delivery, to consider significant improvements in vehicle routing to a specific company, considering that the integration and optimization of these services can reduce costs.